The relationship between distribution of the genera Tomares Rambur, 1840 and the distribution of the larval host plant Astragalus L. (Turkey) (Lepidoptera: Lycaenidae) - Selma Seven Çaliskan; Fatma Yıldız (SHILAP)
The aim of this study is to reveal the patterns that shape the current distribution of the genus Tomares Rambur, 1840 in Turkey. For this purpose, the relationship between the distribution of the larval food plant Astragalus species of the genus Tomares was examined. For this reason, the data of Astragalus species preferred by larvae were investigated. Larvae of Tomares prefer 14 species of the genus Astragalus as food plants. Only seven of them are distributed in Turkey: Astragalus ponticus Pall., A. utriger Pall., A. macrocephalus Willd., A. micropterus Fisc., A. ornithopodioides Lam., A. densifolius Lam, A. physodes L. The connection between the distribution areas of the Tomares species and Astragalus species in Turkey are discussed.